Specific bile salt hydrolase genes in Lactobacillus plantarum AR113 and relationship with bile salt resistance. (June 2021) - Wang, Guangqiang; Yu, Huaning; Feng, Xin; Tang, Hongyu; Xiong, Zhiqiang; Xia, Yongjun; Ai, Lianzhong; Song, Xin
Abstract: The resistance of probiotics to bile salts is critical to their survive in the intestinal tract. Bile salt hydrolase (BSH) catalyzes the deconjugation of conjugated bile salts and is thought to be involved in bile salt resistance. The aim of this study was to explore the roles of different bsh genes in the bile salt resistance of Lactobacillus plantarum AR113. CRISPR-Cas9 gene editing was used to construct single, double, and triple bsh knockout strains. The functions of the bsh 1, and bsh 3 genes were found to be critical for BSH activity in L. plantarum AR113. Examination of six bile salts revealed that glycine-conjugated bile salts were the preferred substrate of BSH. The growth of strains with bsh1 or bsh3 knockout was significantly inhibited when treated with glycine-conjugated bile salts. However, strains with bsh2 or bsh4 knockout were not affected. These results suggested that bsh 1 and bsh 3 are closely related to bile salt resistance. This result will be useful for the rational, high-throughput selection of strains with high tolerance to bile salts. Highlights: bsh 1 and bsh 3 are critical for BSH activity in Lactobacillus plantarum AR113. glycine-conjugated bile salts are the preferred substrate of BSH. bsh 1 and bsh 3 are closely related to bile salt resistance.